Management of Acute Seizures and Status Epilepticus in Children - R.M. Indra (HM Publisher, 2018)
Seizure and status epilepticus (SE) are most common pediatric neurological emergencies, which can result in mortality and long-term disabilities. Status epilepticus is defined as prolonged epileptic seizure that may result in permanent damages to central nervous system, usually after 30 minutes or more for convulsive SE. In 2016, American Epilepsy Society has developed an evidence-based guideline for the management of SE, and in the same year, the Indonesian Pediatric Society published a recommendation for management of SE which was tailored to specific condition and availability of drugs in Indonesia. First line of SE management generally consists of benzodiazepine, usually rectal diazepam, intramuscular, buccal midazolam or intranasal preparations with an assumption that intravenous access has not been established. Second line of management consist of intravenous phenytoin, phenobarbital, levetiracetam, and valproic acid, some not available in Indonesia. About 90% of cases can be controlled with these two lines of drugs, the rest are categorized as refractory SE and require intensive care.